(untitled) (Qualitative Research Journal for Social Studies, 2025)
E-learning is called electronic learning, in which learners get education by electronic devices. This method of learning has become more popular in the COVID-19 era. However, it is essential even after COVID-19 era. This particular study aims to investigate e-learning processes during and after COVID-19, to scrutinize the influence of e-learning and analyze the challenges faced by learners. A quantitative research method is employed in this study. A close-ended questionnaire is used as a tool for collecting data. An online Google form is used to prepare a questionnaire. This form is sent to the students using the snowball technique. The sample size is 340. The participants are students of different universities and colleges in Punjab, Pakistan. A random sampling technique is used for the purpose of data collection. Data are analyzed through pie charts. The study’s results present the methods and influence of E-learning along with the challenges faced by students who were getting education online.